2008
DOI: 10.1021/jf801028g
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Identification of Oligomers from Partial Degradation of Lime Fruit Cutin

Abstract: Complementary degradative treatments with low-temperature hydrofluoric acid and methanolic potassium hydroxide have been used to investigate the protective biopolymer cutin from Citrus aurantifolia (lime) fruits, augmenting prior enzymatic and chemical strategies to yield a more comprehensive view of its molecular architecture. Analysis of the resulting soluble oligomeric fragments with one- and two-dimensional NMR and MS methods identified a new dimer and three trimeric esters of primary alcohols based on 10,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 29 publications
3
36
1
Order By: Relevance
“…The cuticle forms a continuum with the cell wall and may be covalently linked to the cell wall (Sitte and Rennier, 1963;Jeffree, 2006;Tian et al, 2008).…”
Section: The Localization and Ultrastructure Of Diffusion Barriers Thmentioning
confidence: 99%
See 2 more Smart Citations
“…The cuticle forms a continuum with the cell wall and may be covalently linked to the cell wall (Sitte and Rennier, 1963;Jeffree, 2006;Tian et al, 2008).…”
Section: The Localization and Ultrastructure Of Diffusion Barriers Thmentioning
confidence: 99%
“…In addition, partial polymerization followed by liquid state NMR or GC/MS provides information about the linkages between different monomers within the polymer (Graça et al, 2002;Graça and Santos, 2006;Tian et al, 2008;Graça and Lamosa, 2010). However, these techniques require quantities of material that cannot be easily obtained in Arabidopsis.…”
Section: Lipid-based Diffusion Barriers As Part Of the Cell Wall Contmentioning
confidence: 99%
See 1 more Smart Citation
“…The previous study provides us important information of the genes putatively involved in cuticle formation in citrus fruits by cDNA microarray coupled with laser microdissection [24]. Besides, extensive studies have been focused on the component analysis of cuticle in citrus fruits [25,26]. However, cuticle is established during development and there has been no report of a comprehensive study of cuticle development in citrus fruits.…”
Section: Introductionmentioning
confidence: 99%
“…Linear dimers were identified after partial alkaline hydrolysis of tomato (Solanum lycopersicum) cutin (Osman et al, 1995). NMR and mass spectrometry analyses of oligomers released after partial depolymerization revealed primary and secondary ester linkages between cutin monomers (Graça et al, 2002;Stark and Tian, 2006) as well as covalent linkages between some cutin OH fatty acids and oligosaccharides (Tian et al, 2008). However, it has been shown that partial hydrolysis does not necessarily release all of the representative building blocks of the entire polymer (Deshmukh et al, 2003).…”
mentioning
confidence: 99%